Transiting out of full-time national service: a qualitative study of barriers and motivators of weight change in young adult men in Singapore - Chong, Mary Foong-Fong (2022)
Higher prevalence of obesity in men compared with women, particularly among those 18 to 40 years of age, has been observed in Singapore. We explored young men's perceptions of weight change after transiting out of National Service (NS) over a 12-month period and sought to understand the underlying drivers. In-depth interviews, guided by the Health Belief Model (HBM), were conducted with young men 12 months after they had completed full-time NS. Six constructs from the HBM, namely, perceived susceptibility, perceived severity, perceived benefits, perceived barriers, cues to action, and perceived self-efficacy, were utilized to guide the analysis. Thematic analysis revealed that participants generally perceived a gain in body weight after the transition and attributed this to decreased exercise-related physical activity (PA) levels and increased consumption of unhealthy food. However, many did not display immediate concerns nor view leading a healthy lifestyle as priority, citing time constraints, inertia to comply, or lack of access to sports facilities and healthy food options as barriers. Healthy lifestyle behaviors, mainly PA, were mostly pursued for physical health and appearance. Motivators toward a healthy lifestyle tended to be internal factors such as self-motivation, personal preference, and habit, whereas external motivators included peer or familial influence and environmental factors. Our findings align with key concepts of the HBM and suggest a need to educate young men transiting out of NS on lifestyle, weight, and health, in particular addressing their misconceptions.